Farmacocinética da gentamicina asministrada pela via intravensa regional em equinos com a utilização de modelos de torniques - Rodrigues, Karoline Alves [UNESP] (2014)
The horses are often affected by septic processes in the distal portions of the limbs. Among the various therapeutic approaches, there is intravenous regional perfusion of antimicrobials (IRPA) used as an option to combat local infection. The technique aims to provide a high concentration of the drug in the affected area. The procedure is based on placing a tourniquet proximal to the infected area in the region of providing the venous and arterial blood flow occlusion, allowing the drug to remain on the affected area at least 30 minutes. Among the antimicrobial agents indicated for IRPA, highlight the gentamicin sulfate. The objective of this study was to evaluate and compare the pharmacokinetics of gentamicin in plasma and synovial fluid of carpal joint of horses undergoing IRPA using two models of tourniquets. Were used ten healthy equines, randomly divided into two groups of five animals, the tourniquets were applied in the middle third of the radius, always by the same applicator. The tourniquet GTT group received latex tube, while the GTE group Esmarch bandage. After positioning the tourniquets, the cephalic vein had been accessed and administered 2.2 mg / kg gentamicin sulfate, added to 40 mL saline q.s.. Prior to placement of the tourniquet, proceeded color Doppler ultrasonographic evaluation in the treated limb for viewing the median artery and cephalic vein. Samples of synovial fluid and blood carpal were obtained in the moments M0, M15 ', M30', M1h, M2h, M4h, M6h, M8h, M12h, M24h and M48h to perform the analysis of concentration of gentamicin by high-performance liquid chromatography (HPLC), as well as calculations of pharmacokinetic parameters in monocompartiment model. No significant differences in pharmacokinetic parameters were found between treatment groups (P>0.05). The results showed that the two types of tourniquets in IRPA can be used in a proximal region of forelimb in horses, if applied properly, both are capable of ...